"It has changed my life": unconditional cash transfers and personalized infant feeding support- a feasibility intervention trial among women living with HIV in western Kenya - Emily L. Tuthill; Ann E. Maltby; Belinda C. Odhiambo; Thomas J. Hoffmann; Maureen Nyaura; Rosemary Shikari; Craig R. Cohen; Sheri D. Weiser (BMC, 2023)
Abstract Background The syndemic effects of poverty, food insecurity and living with HIV are recognized as global health priorities, including through the United Nations Sustainability Goals 1, 2 and 3. Today, women and girls account for 63% of all new HIV infections in eastern and southern Africa, including Kenya. Pregnant and postpartum women living with HIV in this setting face unique challenges including increased financial insecurity as women leave the work force to care for their newborn infants. This contributes to poverty, food scarcity and stress. Methods To address financial insecurity, improve infant feeding and reduce stress among mothers living with HIV in this setting, we developed a multilevel intervention, Supporting Healthy Mothers, consisting of 10 monthly unconditional cash transfers (10,000 KES, ~$75 USD/month) and personalized infant feeding support from pregnancy to 7 months postpartum. We conducted a non-randomized feasibility trial of this intervention among women engaged in HIV care in Kisumu, Kenya. From February 23, 2022 to March 23, 2022, we enrolled a total of 40 women who were 20-35 weeks pregnant-20 women to the intervention group at a public clinic, and 20 women to the control group at a similar clinic. Our aim was to assess feasibility, acceptability, and the potential impact of the intervention on food security, infant feeding and maternal mental health. Results Analyzing data from all 40 participants, we found a significant reduction in food insecurity scores from baseline for the intervention group when compared to the control group at 6 weeks and 6 months postpartum (p = 0.0008 and p < 0.0001, respectively). Qualitative exit interviews with intervention group participants confirmed women felt more financially secure and had newly acquired practical knowledge and skills related to infant feeding. Women found the two intervention components highly acceptable and described an overall positive impact on wellbeing. Conclusions The Supporting Healthy Mothers intervention has potential to positively impact women across the perinatal period and beyond by increasing financial security and supporting women to overcome infant feeding challenges and should be assessed in larger trials. Trial registration Supporting Healthy Mothers was registered with ClinicalTrials.gov Protocol Registration and Results System, initially published on February 1, 2022. ClinicalTrials.gov ID: NCT05219552 Protocol ID: K23MH116807.